Measuring up: Rasch analysis of English reading comprehension test for informal education learners - Rachmawati, Arandha May; Widyantoro, Agus (English Language Teaching Educational Journal, 2025)
This study aims to evaluate the quality of English reading comprehension test instruments used in informal learning, especially as English literacy tests. With a quantitative approach, the analysis was carried out using the Rasch model through the Quest program on 30 multiple-choice questions given to 30 grade IX students from informal educational institutions in Bantul. The results of the analysis showed that although all questions were included in the fit category for the Rasch model, the level of reliability was relatively low, that was 0.52 for items and 0.39 for participants. In addition, 13.3% of the questions showed inconsistent results (misfit), this means that there is inconsistency in the results and quality of the questions that need to be improved. The analysis of the level of difficulty also showed that there were questions that were too easy or too difficult. These findings highlight the importance of revising the test items and the need to increase the number of participants and items to obtain more accurate measurement results. This study also provides practical implications regarding the need for continuous and planned instrument development in the context of informal education, to provide valid and reliable evaluation tools to measure students' literacy skills.